Water management and problems involved - Astorquiza I. (Agriculture, durabilité et environnement, 1995)
In order to approach the management of a resource such as water, one must first of all consider the institutional framework which affects the resource, together with the underlying ownership structure. The different institutional frameworks and their corresponding regulations imply different resource allocations whose efficiency and equity will need to be considered, besides their effects on the sustainability of the resource over time. Once the conceptual framework has been explored, water management in Spain will be analysed.
Séminaire de l'Association Tunisienne des Anciens de l'Institut Agronomique Méditerranéen de Zaragoza (ATA-IAMZ), 1993/12/02-03, Tunis (Tunisia)